1995
DOI: 10.1159/000264258
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Mild Hydronephrosis and Chromosomal Defects: Relation to Maternal Age and Gestation

Abstract: The presence of multiple ultrasonographic abnormalities is associated with a significantly increased risk of chromosomal defects, while for isolated abnormalities, the association is less clear. In a study of 1,177 fetuses with mild hydronephrosis at 16-26 weeks of gestation, the fetal karyotype was abnormal in 86 (7.3%) of the cases and the most common chromosomal defects were trisomies 21,18 and 13. The frequency of chromosomal defects increased with the number of additional abnormalities and for each chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
4
10
1
1
Order By: Relevance
“…Our own analysis is consistent with this risk, although this risk may not be increased when pyelectasis is isolated. The lack of association as an isolated finding has also been suggested by other studies, 102,103 although one center has shown an association as an isolated finding. 104 …”
Section: Renal Pyelectasissupporting
confidence: 72%
“…Our own analysis is consistent with this risk, although this risk may not be increased when pyelectasis is isolated. The lack of association as an isolated finding has also been suggested by other studies, 102,103 although one center has shown an association as an isolated finding. 104 …”
Section: Renal Pyelectasissupporting
confidence: 72%
“…In our high‐risk population, associated anomalies were seen in 8% of cases. In other studies16–18 this percentage varied between 3.9% and 31.6%. The relatively high percentage of associated anomalies in the present study is likely to be due to the fact that a high‐risk population was investigated.…”
Section: Discussionmentioning
confidence: 74%
“…To date, the association between isolated pyelectasis is unresolved. While some studies reported an association (Corteville et al , 1992; Nicolaides et al , 1992; Wickstrom et al , 1996a, 1996b; Chudleigh et al , 2001) when pyelectasis occurred in the absence of other congenital malformations, others have found no such association (Snijders et al , 1995a; Vintzileos and Egan 1995; Nyberg et al , 2001; Havutcu et al , 2002; Coco and Jeanty 2005). Reported likelihood ratios have also varied among previous published studies.…”
Section: Introductionmentioning
confidence: 99%